(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This research investigates and evaluates the impact of Organizational Citizenship Behavior (OCB) and job satisfaction on employee performance within a BUMD office in Cirebon Regency. Quantitative research methods were utilized in this study, involving the distribution of questionnaires. The sample group was comprised of 240 full-time employees. By applying the Slovin formula with a margin of error of 5%, a total of 150 participants were selected from a BUMD office in Cirebon Regency. This study utilized statistical analysis methods to investigate how Organizational Citizenship Behavior and Job Satisfaction impact the performance of employees. Statistical analysis was performed using t-test and F-test methodologies. The results of the t-test show a strong correlation between Organizational Citizenship Behavior (X1) and employee performance (Y). Furthermore, the F-test results suggest that Organizational Citizenship Behavior (X1) and Job Satisfaction (X2) together have a significant influence on employee performance. It was found that Organizational Citizenship Behavior (X1) has a considerable positive impact on employee performance (Y), while Job Satisfaction (X2) also plays a crucial role in improving performance outcomes. Workers who exhibit elevated levels of both OCB and job satisfaction tend to demonstrate enhanced performance results. Consequently, to maximize employee performance effectiveness, organizations should prioritize creating workplace conditions that promote Organizational Citizenship Behavior and enhance overall job satisfaction among their workforce.